In situ carbon mineralization in ultramafic rocks: Natural processes and possible engineered methods. (July 2018) - Kelemen, P.B.; Aines, R.; Bennett, E.; Benson, S.M.; Carter, E.; Coggon, J.A.; de Obeso, J.C.; Evans, O.; Gadikota, G.; Dipple, G.M.; Godard, M.; Harris, M.; et al.
Abstract: In this invited review, we summarize the main results of ongoing research on " in situ " carbon mineralization in ultramafic rocks, including outcrop studies in Oman (e.g., [1, 2]), investigation of carbon mass transfer in subduction zones from the Oman Drilling Project (e.g., [3-7]), laboratory investigations (e.g., [8-12]) and numerical modeling (e.g., [13-17]) of the pressure of crystallization and reaction-driven cracking, and assessment of the rate, cost and capacity of various proposed methods for engineered carbon mineralization [18, 19].